2008
DOI: 10.1016/j.healthplace.2007.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Whither gender in urban health?

Abstract: The past decade has witnessed the rapid expansion of the field of urban health, including the establishment of an international society of urban health and annual conference, the publication of several books and the growing popularity of a peer-reviewed journal on urban health. Relatively absent is an emphasis on the role of gender in urban health, despite scholarly and theoretical work on gender and place by feminist geographers, sociologists, public health researchers and others. This essay examines the trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Adding to current debates about differential place effects by gender (Frye et al, 2008), we also found wider area differences in old-age for men than for women, although overall, women were more likely to report poor health at an earlier age than men. These findings were robust for control for period effects and length of residence.…”
Section: Discussionmentioning
confidence: 51%
“…Adding to current debates about differential place effects by gender (Frye et al, 2008), we also found wider area differences in old-age for men than for women, although overall, women were more likely to report poor health at an earlier age than men. These findings were robust for control for period effects and length of residence.…”
Section: Discussionmentioning
confidence: 51%
“…Population aging is emerging as a pressing issue for health and social services globally (Kasl 1997;World Health Organization 2003). Gender is a dynamic and socially defined construct comprising role enactment, values and beliefs of both men and women (Frye, Putnam et al 2008). Gender-based roles, enactment and health outcomes are shaped by social, economic, political and cultural factors, rather than by biology alone (Raymond, Greenberg et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Although policy makers globally are attuned to the needs of the aging population, the focus on the needs of women specifically is more confined to non-government organizations, rather than peak government bodies, and as a consequence the unique needs of women are less visible in population planning and policy (World Health Organization 2005). It can be argued that the increasing numbers of women in the aging population requires a reframing of the way we view the planning and delivery of health care services to reflect a gendered approach (Frye, Putnam et al 2008). Globally, the need to address the health outcomes of women has been recognised.…”
Section: Introductionmentioning
confidence: 99%
“…"Using my own power out of the disease shackle" was the core category referring to elderly women who coexist with chronic illnesses. Elderly women should be provided with individually targeted plans for disease management and health maintenance to enable them to participate in health care decisions at the onset of chronic diseases.The increasing number of women in the aging population requires a reframing of how people view the planning and delivery of health care services to reflect a gendered approach (Frye, Putnam, & O'Campo, 2008). As women age, they frequently experience multiple chronic and complex health conditions, such as heart disease and arthritis, which affect their health and well-being (Davidson et al, 2003).…”
mentioning
confidence: 99%
“…The increasing number of women in the aging population requires a reframing of how people view the planning and delivery of health care services to reflect a gendered approach (Frye, Putnam, & O'Campo, 2008). As women age, they frequently experience multiple chronic and complex health conditions, such as heart disease and arthritis, which affect their health and well-being (Davidson et al, 2003).…”
mentioning
confidence: 99%